SIKAP, KEPUASAN, DAN LOYALITAS KONSUMEN TERHADAP PRODUK SARI APEL UMKM APELNESIA, KOTA BATU DENGAN PENDEKATAN BAURAN PEMASARAN 4P - Muhammad Rifky Setiadi; Febriananda Faizal; Destyana Ellingga Pratiwi (Lampung University, 2021)
Massive apple production drives MSMEs in Batu City to process the fruit, as an example, apple extract. With so many MSMEs that make apple extract, creates higher market competitiveness. One of the MSMEs that makes apple extract is Apelnesia. The purpose of this research is to study attitude, satisfaction, and loyalty of consumers towards Apelnesia MSME apple extract product. The basic method of this research is a quantitative analysis. The sampling method uses non-probability method with time linear function technique. This research uses Fishbein analysis, Importance Performance Analysis, Customer Satisfaction Index, and Loyalty Pyramid. The results showed that consumer attitude is Quiet Positive. Importance Performance Analysis showed the attributes that needs improvement i.e. Packaging (X1.4), Price equals quality (X2.1), Easy product access (X3.1), and Strategic location (X3.3). Satisfaction level of consumers according to Customer Satisfaction Index is Satisfied. Loyalty Pyramid showed that the highest level of consumer loyalty is Liking the brand with 71.88%.Key words: apple extract, attitude, loyalty, marketing mix, satisfaction